Using Failure Mode and Effect Analysis (FMEA) in the Risk Analysis of Industrial Poultry Production for Decreasing Threats of Poultry by Analyzing Points of Failure - Nikpay , Amir Abbas; Zaghi, Danial; Kohan, Idin Zojaji; Tavakol, Mona (International Journal of Poultry Science, 2014)
Regarding existence of different diseases such as gastrointestinal diseases, applying an appropriate diet is important. Poultry industry plays a significant role in this field. Therefore, sustainable and safe production in this industry is a necessity and this fact will not be possible; unless we minimize environmental pollution; improve quality and safety of poultry products; use optimally green and environmentally friendly resources; decrease use of nonrenewable resources, manage superfluous resources. All these facts; employing expert personnel, can help us achieve a healthy system in food and production. Today, poultry industry aims to process chicken without using antibiotics and chemicals. In this study we tried to define point of failure, analyze the effect of implying appropriate corrective actions applying failure modes and the effects analysis method (FMEA). Also, applying FMEA, we considered different aspects of risks and analyses. In order to decrease and test the risks and decrease deplorable threats, sustainable production has been analyzed in a defined period.